Conservation Status Assessment of the Egg-mimic Darter (Percidae: Etheostoma pseudovulatum) Using a Multi-faceted Approach - Zachary L Wolf; John W Johansen; Rebecca E Blanton (Southeastern Fishes Council Proceedings, 2022)
The imperiled Egg-mimic Darter (Etheostoma pseudovulatum) is a headwater-adapted fish restricted to an area less than 1000 km2 in Tennessee. It is found in only six tributaries of the Duck River and the large, mainstem of this system may act as a barrier to dispersal, restricting population connectivity. The only status assessment of this species was over two decades ago; genetic diversity and the degree of population connectivity have never been evaluated. We conducted a conservation status assessment using a multi-faceted approach to better inform conservation management plans, including examining its current distribution, assessing habitat quality, estimating abundance, population size and haplotype diversity, and evaluating historical population connectivity. Surveys were conducted in spring and fall (2014) and population size was estimated using the Petersen mark-recapture method at a subset of localities, which were then regressed to obtain population estimates at all localities. Haplotype diversity and population connectivity were examined using the mitochondrial ND2 gene. The Egg-mimic Darter was present at all localities and was relatively abundant, comparable to historical observations. Habitat quality did not appear to be substantially degraded. Overall haplotype and nucleotide diversity were low compared to widespread darters and comparable to other imperiled darters; however, demographic analyses indicated the species has remained stable over contemporary and historical timeframes. The Egg-mimic Darter has likely maintained gene flow historically at five of the six tributary systems, suggesting the mainstem Duck has not been a long-standing barrier to dispersal. One haplotype was shared across all tributary systems except Beaverdam Creek, which had a largely unique assemblage of haplotypes. Overall, the conservation status of the Egg-mimic Darter appears to be stable. However, we recommend regular monitoring with special consideration given to smaller tributary systems and the genetically distinct Beaverdam Creek population. Even though there was evidence of historical population connectivity, the risk of local extirpation remains, considering the small population sizes in several tributary systems. We also recommend assessments of contemporary genetic structure and population connectivity.
Keywords: darters; mitochondrial DNA; population size; population connectivity; conservation